MANAJEMEN PENDIDIKAN BERBASIS INFORMASI DI ERA SOCIETY 5.0 - Hermawansyah Hermawansyah (Prodi PAI STIT Sunan Giri Bima, 2022)
In the era of information system development, it will be seen that the orientation of future education is so fast, so that education management is the most important in education and is also most needed, because the education management information system is a supporting factor for the progress of formal and informal educational institutions so that in an effort to implement an education management information system, it cannot be supported. by the employee's own performance manually. because in the era of the industrial revolution 4.0, there have been changes in the education management sports system, more so on the declaration of Society 5.0 as a wide door for the community to solve problems, so that improving the quality and public services related to the management of quality school education information in the service process to the school also needs to This needs to be considered so that it is necessary to apply an education management information system which is one of the important factors in the quality of education and of course also helps all levels of teachers, administrative staff in improving quality in schools, especially the community.